Conditional effects of state fear of negative evaluation on restrictive eating behaviors. (December 2022) - Mancuso, Christopher J.; Spoor, Samantha P.; Kambanis, P. Evelyna; De Young, Kyle P.
Abstract: Fear of being evaluated negatively by others is a risk factor for the development of disordered eating. Specifically, trait level fear of negative evaluation (FNE) predicts disordered eating severity above other social anxiety traits. However, it remains unclear how state levels of this fear may impact eating behavior. The current study aimed to examine this risk factor in the context of state-level eating behavior. We hypothesized that: (a) elevated levels of state FNE would enhance the relationship between restraint and restriction and (b) we sought to explore the predictive nature of high trait FNE on restriction. Study procedures for N  = 64 undergraduate students included assessment of dietary restraint, fear of negative evaluation, and hypothetical meal choice in the context of several proposed social and non-social settings. Results indicated that higher state FNE was related to more restrictive food choice across settings, and levels of trait FNE were not related to food choices. State FNE did not enhance the relationship between restraint and restriction. This project sought to examine the degree to which fear of negative evaluation impacts the relationship between dietary restraint and restriction, testing a unique risk factor for the development of eating psychopathology. Highlights: Higher state FNE was related to more restrictive food choice across, and levels of trait FNE were not related to food choices State FNE did not enhance the relationship between restraint and restriction